Screening and characterization of protease-producing Virgibacillus, Halobacillus and Oceanobacillus strains from Thai fermented fish - Thanapun Taprig, Ancharida Akaracharanya, Jaruwan Sitdhipol, Wonnop Visessanguan and Somboon Tanasupawat (Journal of Applied Pharmaceutical Science, 2013)
Halophilic bacteria from fermented fish (pla-ra and pla-chom), shrimp paste (ka-pi) and fermented crab were isolated and screened for protease activities. Twenty-seven isolates exhibited protease specific activities ranged from 0.12 to 3.62 unit/mg protein. Isolate TPPN2-1 from pla-ra produced maximal protease specific activity (3.62 units/mg protein). They were Gram-positive, moderately halophilic rod-shaped bacteria and were divided into 5 groups on the basis of their phenotypic and chemotaxonomic characteristics, DNA-DNA relatedness including the 16S rRNA gene sequences analyses. Three isolates (Group I) were identified as Virgibacillus halodenitrificans, 3 isolates (Group II) as V. marismortui, 7 isolates (Group III) as V. dokdonensis, 10 isolates (Group IVA & IVB) as Halobacillus species and 4 isolates (Group V) as Oceanobacillus iheyensis.
Keywords: Fermented fish, Virgibacillus, &l